A Feasibility Study on Needle Safe Hypodermic Syringe Disposer - Dinglasan, Criselda C.; Gaza, Rhett D. C.; Rosario, Michael B.; Torres, Gwen P. (Diliman, Quezon City College of Engineering, 1999)
The "Needle Safe" Hypodermic Syringe Disposer is a new invention to be introduced to the market. "Needle Safe's" main purpose of the destruction of used syringes. It is a simple machine with simple parts and is relatively easy to operate. Its main parts are the Milling Assembly, which destroys the barrel of the syringe and the Copper Brush Assembly, which melts the needle of the syringe. : Needle Safe has an overall weight of 7.27 kilograms and has dimensions of 31 x 27 x 19 centimeters. The project aims to produce and sell 1,869 units for its initial year for a market share of 30%. Production levels will increase yearly which is determined by increasing the market share for each succeeding year by 1%. The target market of the project is composed of the secondary hospitals, tertiary hospitals and rural health centers located in all the regions in the Philippines. With a market area of dispersion as wide as this, an effective channel of distribution will be on hand. For this, the project taps local distributors to help sell the product in the other region in the Philippines. Aside from this, the project will also employ sales representatives to demonstrate the product and its uses to the hospitals in the different regions. To further stimulate demand and attract potential buyers from the whole archipelago, an aggressive promotional and advertising campaign will be launched. This is composed of printed advertisements in newspapers and trade magazines, distributions of posters and brochures to hospitals nationwide, and hospital sampling to be conducted by sales representatives. This campaign will amount to a total of P458,012.00 for the first year. The production processes involve to manufacture"Needle Safe" are very simple. It is composed of Metal Casing Fabrication, Blade and Slat Assembly, Copper Brush Assembly and the Main Assembly. Several equipment and tools sourced locally will be used to support and carry out the processes. These include the power press, shear cutter bending machine and welding machines. The monthly production will be done in an average of 22 working days per month using one 7.5 hour shift per working day; 5 workers will man the production floor and 1 worker each will be assigned to other tasks such as quality control and delivery. The entire plant made up of the main production area, the office space and warehouse will occupy a total of 261 m2. A 300m2 lot with existing facilities situated in E. Rodriguez, Marikina City has been identified as the site of the plant. The total project cost made up of the total fixed investments, six - month working capital and 10% contingency allowance is estimated at P6,997,761.79. An analysis of the income statement using 6 months working capital yields a positive net income for the project thus becoming the total amount to be invested in the project. Forty percent of this amount will be loaned through the Development Bank of the Philippines with annual loan payments for a 10-year loan term at 17.5 interest. The remaining amount of 4,198,657.08 will be raised through equity. Cash flow projections showed that the investment will be completely recovered in 3 years and 6 months time, with a 49% internal rate of return. The project will be established as a corporation because of the various advantages it has over the other forms of ownership. Aside from the 8 production workers, 15 more employees will comprise the office and support staff. The entry of ?Needle Safe? into the local medical equipment industry will give the government a total of approximately P3.3 million annually in taxes, generate 23 more employment opportunities and reduce possible transmission of diseases caused by accidental pricks of contaminated needles. With all these facts and figures, the manufacture of "Needle Safe" Hypodermic Syringe Disposer is an economically feasible and attractive business venture.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Medical supplies, Disposable; Health facilities--Waste disposal; Health facilities--Waste disposal--Health aspects; Participatory monitoring and evaluation (Project management)